Biomass yield in production systems of soybean sown in succession to annual crops and cover crops - Pacheco, Leandro Pereira; São Miguel, Andressa Selestina Dalla Côrt; da Silva, Rayane Gabriel; Souza, Edicarlos Damacena de; Petter, Fabiano André; Kappes, Claudinei (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the biomass (leaves and stems) production of annual and cover crops sown as second crop, and its effects on soybean yield in succession. The experiment was carried out in the 2014/2015 and 2015/2016 crop seasons. Soybean was sown in the crop season and in the second crop, in a randomized complete block design, in nine production systems (treatments) consisting of annual crops (corn, sunflower, and cowpea) and cover crops (Pennisetum glaucum, Crotalaria breviflora, C. spectabilis, Urochloa ruziziensis, Cajanus cajan, Stylosanthes sp., and U. brizantha), which were grown in monocropping or intercropping systems, besides fallow as a control. Monocropped P. glaucum and U. ruziziensis showed a faster establishment and growth of plants, higher-total biomass and soil cover rate in the 2014 crop season. In 2015, corn intercropped with U. ruziziensis and C. spectabilis, and sunflower with U. ruziziensis stood out for total biomass production during flowering and after harvesting of corn and sunflower grains. Biomass composition in the systems showed greater proportions of stems than of leaves, and C. spectabilis stood out after senescence. Sown as a second crop, C. spectabilis promotes yield increase of soybean grown in succession in the no-tillage system.